(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
FinTech is being used more and more to improve customer service. The use of online and mobile banking platforms has increased in response to increased demand for financial digital services. However, in the banking industry, customers’ fear of using FinTech varies across demographics, like Age Gender, Education, and Income. This study focused on the Technology Acceptance Model (TAM) to explain the effects of customers’ demographics and the mediating effect of trust, risk, perceived ease of use, and perceived usefulness of FinTech and customers’ attitudes on the banks’ customers’ intention to adopt FinTech. For collecting data, a structured questionnaire was shared among the 1000 bank customers through a Google form link. A total of 550 responses were received, after discarding incomplete or wrongly filled questionnaires, and the final sample of 455 responses was analyzed in smart PLS. technique. The structured equation model (SEM) analysis reveals that customers’ intent to utilize FinTech is significantly influenced by their attitude toward adopting new technology in the banking industry. The results also establish a significant impact of age, income, education, perceived ease of use, trust, and risk on the customers’ attitude toward adopting new FinTech services. Moreover, SEM analysis shows that PEOU, PU, Trust, and risk mediate the relationship between the customers’ demographics and their attitude toward using FinTech services. The findings of this study support the TAM postulates and suggest that policymakers should consider the demographic impact on the use of FinTech services and should focus on developing a more user-friendly and secure FinTech interface